Modulation of mitochondrial outer membrane permeabilization and apoptosis by ceramide metabolism - Rego, António (2012)
The yeast Saccharomyces cerevisiae undergoes a mitochondrial-dependent programmed cell death in response to different stimuli, such as acetic acid, with features similar to those of mammalian apoptosis. However, the upstream signaling events in this process, including those leading to mitochondrial membrane permeabilization, are still poorly characterized. Changes in sphingolipid metabolism have been linked to modulation of apoptosis in both yeast and mammalian cells, and ceramides have been detected in mitochondria upon apoptotic stimuli. In this study, we aimed to characterize the contribution of enzymes involved in ceramide metabolism to apoptotic cell death induced by acetic acid. We show that isc1Δ and lag1Δ mutants, lacking inositol phosphosphingolipid phospholipase C and ceramide synthase, respectively, exhibited a higher resistance to acetic acid that was associated with lower levels of some phytoceramide species. Consistently, these mutant cells displayed lower levels of ROS production and reduced mitochondrial alterations, such as mitochondrial fragmentation and degradation, and decreased translocation of cytochrome c into the cytosol in response to acetic acid. These results suggest that ceramide production contributes to cell death induced by acetic acid, especially through hydrolysis of complex sphingolipids catalyzed by Isc1p and de novo synthesis catalyzed by Lag1p, and provide the first in vivo indication of its involvement in mitochondrial outer membrane permeabilization in yeast.